Blast Resistance of Non-Composite Tilt-Up Sandwich Panels and their Connections" - Barreiro, Jose (Université d'Ottawa / University of Ottawa, 2016)
Blast risk associated with terrorist threats and accidental explosions has become an international concern over the past decade and has provoked structural engineers to implement protective design measures. Recent advances in this area of research has seen tremendous improvements in mitigating this risk through the installation of retrofits, advanced structural design, or pre-emptive protective measures. Tilt-up and precast panel walls are constructed using a unique approach in which the walls are cast horizontally and lifted, or tilted, into their final vertical position. These unique structures are cost effective, energy efficient, and can be rapidly constructed. This approach is commonly applied to the construction of large industrial facilities and the construction of schools which are categorized as high importance structures in the National Building Code of Canada. These panels are inherently flexible and have a surplus of mass making them desirable for protective design applications, however their behaviour under blast induced loads is not well defined. This experimental research project investigates the behaviour of non-composite tilt-up sandwich (NCTS) panels and solid reinforced concrete (SRC) panels with realistic support conditions subjected to blast-induced shockwaves. Previous research shows that NCTS panels, identifiable by their large structural wythe, exhibit some degree of composite behaviour and require between 5% to 10% composite action for successful erection. Five scaled specimens were constructed following common procedures used in practice, equipped with identical data acquisition instruments, and tested at the University of Ottawa shock tube testing facility under similar blast pressure-impulse combinations. Test results for the NCTS and SRC panels are compared graphically in terms of displacement–time histories and sectional strain distributions. The data is evaluated to approximate the composite behaviour at mid-span of the NCTS panel. Analytical results generated, using “RC Blast,” single-degree-of-freedom analysis software developed at the University of Ottawa, were validated with empirical data and are presented graphically. Each specimen was equipped with connections similar to those commonly used in the construction of NCTS panels. These connections were experimentally studied under simulated blast pressures and analysed using CSA A23.3-04 guidelines for punching shear capacity. Modified support iii | P a g e reinforcement layouts and surface bonded FRP laminates were evaluated as strengthening and retrofit techniques to prevent support failure. Dynamic support reactions and predicted support resistances are tabulated for each shot of every panel. The results indicate that it is possible to accurately predict the flexural behaviour and support resistance of a NCTS panel using RC Blast and CSA A23.3-04 guidelines. Several factors considered in this analysis include boundary conditions, dynamic material properties, and shear tie degradation. This analysis of flexural behaviour is highly dependent on shear stiffness, which is directly related to the composite action within NCTS panels. Support resistance was increased significantly through application of the strengthening techniques outlined in this thesis.
Keywords: Blast; Tilt-Up; Sandwich Panel; Concrete; Connections